Pregnancy and live birth rates in women with endometriosis related infertility in Latvia - Avdotina, Jekaterina; Mezecka-Oleinika, Aleksandra; Silina, Vija; Vitina, Zane (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Women with endometriosis experience painful symptoms and/or infertility, others have no symptoms at all. According to European Society of Human Reproduction and Embryology guidelines, surgery and assisted reproductive technologies (ART) are an appropriate treatment in cases of endometriosis-associated infertility. There are controversial data on the results of surgery and ART in patients with endometriosis. Methods: Retrospective analysis including 99 infertile patients aged between 25 and 48 years old. All of them had laparoscopic surgery as the primary option. 51 of them undergoing in vitro fertilization or intracytoplasmic sperm injection or frozen embryo transfer from 2003 through 2018 at SIA ‘Clinic EGV’. Results: The mean age of women was 34.2±4.5. In 56 (33.5%) cases was only surgery with 28 (50.9%) biochemical pregnancies and 26 (48.1%) live birth. In 111 (66.5%) cases there were surgery with ART with 48 (47.6%) biochemical pregnancies and 23 (22.7%) live birth. In 1 group patients mean age 30.7±4.6 and 2 group with mean age 35.1±4.2 (p=0.000). It was found that there is significant difference between endometriosis phenotype, infertility type, duration of infertility, repeated laparoscopic surgery, ART cycles, retrieved oocyte count and biochemical pregnancy rate. Conclusions: Patients with endometriosis related infertility should undergo surgical treatment as the primary option. Those patients who do not become pregnant after surgery must be treated with assisted reproductive technology. The optimal time to perform ART is first year after endometriosis surgery.